Cholera and Climate: A Demonstrated Relationship - Constantin de Magny, Guillaume* (American Clinical and Climatological Association, 2009)
Vibrio cholerae, the causative agent of cholera, is naturally present in the environment and autochthonous to coastal and estuarine ecosystems. V. cholerae is associated with copepods for its survival and multiplication in the natural environment. Changes in the density of its reservoir may result in modification of the bacterial population size in the environment. In this context, climate and/or environmental changes will influence the emergence of cholera in human populations. Several human pathogens are naturally occurring in the aquatic environment and can pose a threat to public health, including V. cholerae. We present results of a project, the goal of which was to improve the understanding of environmental factors associated with occurrence and distribution of the causative agent of cholera in time and space. The system that was developed provides real-time as well as short-term to seasonal forecasts of the likelihood of occurrence of V. cholerae in the Chesapeake Bay. The system, and potential future improved versions of it, may be useful to public health officials concerned with environmental factors influencing human health.